The ExCITE-BA Trial: Effects of physical activity plus behavioral activation on preserving cognitive function in elderly patients with mild cognitive im-pairment : Protocol for a randomized, controlled, phase II, parallel, single-blinded, superiority trial (Principles and Practice of Clinical Research, 2022)
Introduction: World population has an increased risk of developing basic neurological deterioration and mild cognitive impairment (MCI). Currently, there is no cure or disease-modifying drug for MCI. Thus, non-pharmacological interventions such as physical activity (PA) and behavioral activation (BA) arise as potential treatment options. This study will assess if a program of combined PA and BA (PABA) reduces disease progression in patients over 60 years old with MCI.Methods: This is a randomized, controlled, phase II, parallel, single-blinded, multicenter, superiority trial with two groups. In total, 184 patients will be randomized at a 1:1 ratio and stratified by age, center, and level of education via permuted block sizes to receive: 1) a combination of moderate-to-high in-tensity PABA or 2) sham intervention (low-intensity PA) plus psychological support (active control). The primary outcome will be a change in cognitive function assessed by Montreal Cognitive Assessment (MoCA) from baseline to 12 months. Secondary outcomes include changes in MoCA at 3, 6, and 9 months. Furthermore, at 0, 3, 6, 9, and 12 months, subjects will be tested with the Barthel Index, Short-Form 12 Health Survey (SF-12), and Geriatric Depression Scale (GDS-15).Conclusion: The study aims to refine treatment options for MCI and uncover directions for different therapeutic approaches. This will be the first randomized clinical trial to establish the efficacy of PABA compared to active control in the progression of MCI. This study could optimize MCI treatment and help alleviate patients, families, and the healthcare system.Keywords: Cognitive Impairment, Exercise, Physical Activity, Behavioral Activation, Study Protocol, Study Design